A extensão no Instituto Federal Sul-rio-grandense: uma construção educativa e cultural na perspectiva das demandas sociais (2014 - 2019) - Fernandes, Luciana Pinto (Universidade do Vale do Rio dos Sinos, 2022)
The thesis, “Extension at the Instituto Federal Sul-rio-grandense: an educational, cultural and social construction from the perspective of social demands (2014 to 2019)”, consisted of a study about extension actions of the Instituto Federal Sul-rio-grandense (IFSul), developed in interstice of 2014 to 2019. It is proposed to analyze the extension actions in the Institute Federal Sul-rio-grandense and the social demands that intend them to verifying the ways in which they respond to the challenges and local and regional problems. Finally, it is observed that the social demands expressed in the IFSul extension actions are configured from the social integration, insertion in the job market and income generation, knowledge generation and technical and citizen training, in this way, these dimensions guide IFSul extension actions, that have particularities that encourage initiatives as responses to local and regional challenges and problems. Thus, IFSul becomes as an agent that offers to respond to social demands, integrates in the society, come close to different realities, once it promotes local and regional socioeconomic development, engage in inclusion socioeconomic proposals, cultural, intellectual and privileges the democratization of education, research and extension, as a condition of intellectual and cultural advance of the students and the proper society.
Keywords: Instituto Federal Sul-rio-grandense; Extensão; Demandas sociais; Extension; Social demands; ACCNPQ::Ciências Humanas::Educação